2020
DOI: 10.1016/j.ijcha.2020.100663
|View full text |Cite
|
Sign up to set email alerts
|

Association between cardiorespiratory fitness, obesity, and incidence of atrial fibrillation

Abstract: Background The interaction between cardiorespiratory fitness (CRF) and incidence of atrial fibrillation (AF) and the interaction between obesity and incidence of AF have been explored separately. Therefore, we evaluated the association between CRF, body mass index (BMI), and risk of developing AF in a cohort of middle-aged and older US Veterans. Methods Symptom limited exercise tests (ETT) were conducted among 16,397 Veterans (97% male) from January 9,1987 to December 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Both reduced %BF and increased CRF are linked to improvements in obesity‐related disorders and decreases in adiposity‐linked inflammation (85‐87). Indeed, research indicates that a 1‐MET increase in CRF correlates with a decrease in cardiovascular risk factors often comorbid with obesity (i.e., hypertension, metabolic syndrome) of up to 22% and a reduced risk of arrhythmias and heart failure in adults with obesity by at least 6% and 21%, respectively (87‐90). Equally, whereas increased muscle mass is positively linked with a greater resting metabolic rate (i.e., 1 kg of muscle gained equals an increase of ~21 kcal/kg) (81), which is significant for weight loss, improvements in lean mass have been shown to more considerably impact health outcomes by decreasing the risk of metabolic syndrome in WLO by up to 33% (91).…”
Section: Discussionmentioning
confidence: 99%
“…Both reduced %BF and increased CRF are linked to improvements in obesity‐related disorders and decreases in adiposity‐linked inflammation (85‐87). Indeed, research indicates that a 1‐MET increase in CRF correlates with a decrease in cardiovascular risk factors often comorbid with obesity (i.e., hypertension, metabolic syndrome) of up to 22% and a reduced risk of arrhythmias and heart failure in adults with obesity by at least 6% and 21%, respectively (87‐90). Equally, whereas increased muscle mass is positively linked with a greater resting metabolic rate (i.e., 1 kg of muscle gained equals an increase of ~21 kcal/kg) (81), which is significant for weight loss, improvements in lean mass have been shown to more considerably impact health outcomes by decreasing the risk of metabolic syndrome in WLO by up to 33% (91).…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the presence of obesity related disorders, peak exercise capacity will evolve differently in different subjects. 48 , 49 , 50 , 51 Healthy obese subjects undergoing weight loss are more likely to experience a decrease in O 2max and peak work output, because of decreased muscle mass 33 and daily cardiac stress. Following weight loss, lower weight-bearing daily activities lead to less cardiac stress, so before surgery carrying more weight during daily activities may be considered as training which can stimulate muscle work and cardiac stress, 33 but after surgery, BW is lower and this effect on muscle 41 and heart 44 , 52 fades away.…”
Section: The Absolute Value Of O 2maxmentioning
confidence: 99%
“…The knowledge about SDB status in AF patients is important to approximate success rates of interventions. SDB is associated with increased AF recurrence rates after antiarrhythmic drug treatment, electrical cardioversion, and catheter ablation in AF [5] , [6] , [7] . Observational studies and meta-analyses showed that appropriate SDB treatment may improve rhythm control in AF patients [8] .…”
Section: Prevalence and Impact Of Sdb On Af Managementmentioning
confidence: 99%